How constrained? Entry into the French Atlantic ﬁshery through second-hand vessel purchase - van, Putten Ingrid; Quillérou, Emmanuelle; Guyader, Olivier (Elsevier, 2012)
Over the past decades fisheries policies have been mainly aimed at encouraging capacity reduction in over-exploited fisheries. Correspondingly, research has focused on developing incentives to exit fisheries rather than investigating entry behaviour. However, with ageing and also fewer fishery participants, concern regarding sectoral renewal is increasing. The second-hand market is an important entry point for first-time owners because it potentially reduces capital constraints by supplying cheaper vessels than newly built ones. The aim of this study is to test whether new fishers entering the industry face greater capital constraints than fishers already in the industry, taking the second-hand market as our population of interest. We model new entry into the fishing sector using 18 years of French Atlantic fleet data with a logit model. We incorporate trade network variables and family connections indicative of the relationship and connections between market traders potentially reducing capital constraints. As expected, we find that first entry is more likely by younger owners for older and cheaper vessels. This suggests that first-time owners are more capital constrained than fishers already trading on the second-hand market. Capital constraints are reduced by geographical proximity and increased integration into a trading network.
Highlights ► Renewal and entry in the fishing industry is an issue of growing importance. ► The second-hand market is an important entry point for capital constrained owners. ► First-time buyers of second-hand vessels are more capital constrained. ► Younger first-time owners are more likely to enter with older and cheaper vessels. ► Geographical proximity and trading network integration reduce capital constraints.
Keywords: fishing vessels; second-hand markets; French Atlantic; sectoral renewal; capital constraints; trade network